Normativisation and its processes as seen from the neo-functional perspective: Towards science governance - Jedlikowska, Dorota (Journal of Public Governance, 2016)
The paper scrutinises the notion of normativisation as a concept met with only relatively rarely in the sphere of the sociology of science. The normativisation concept is here embodied in the neo-functional perspective, with a view to its relationship with the sociology of science being elaborated more deeply, and new analytical paths provided, in this case in regard to the understanding of science. The work underpinning this paper has sought to help make good the lack of relevant studies in the field of the sociology of science. The material presented comes from literature-based research, while the main axis is put on the highlighting of theoretical relationships between types of normativisation and sociological neo-functional theory in order for the inputs of Gunther Teubner in particular to be better grasped. As is signaled at the end, this paper is ultimately targeted at science governance, though this is in itself a notion requiring additional studies if it is to be viewed in particular contexts.